Lethal and sublethal effects of a synthetic detergent on glucose-6-phosphate-dehydrogenase (G-6-P.D.H) enzyme activity in blood of a fresh water teleost Labeo rohita (Hamilton, 1822) - Chellan, Bijoy; Ramesh, M; Ramanujam, R Manavala (Indian Journal of Fisheries, 2011)
Lethal and sublethal effects of a common house hold detergent ’Green Aerial Micro System’ on Glucose-6-phosphate dehydrogenase (G-6-P.D.H) enzyme activity in blood of Laheo rohita was studied. G-6-P.D.H. enzyme activity showed significant reduction in treatments with both lethal and sublethal concentration of the detergent, however, there was a notable reduction in the inhibition of the enzyme at the end of the 30"^ day of the sublethal treatment.